International congress for the integral study of sport (Fiep Bulletin - online, 2015)
Kindly invited by Prof. Dr. José Pedro Reggi, President of the Organizing committee of the above mentioned congresses and the Argentinian Society of Sports and work medicine, to take part in those international meetings, as an honorary guest, I has the good luck of making the acquaintance of illustrious scientist and pedagogues from argentine and other countries, seeing again old friends and visiting the magnificent city of Buenos Ayres.